2022
DOI: 10.1515/cmb-2022-0133
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review, meta-analysis and economic evaluation on Neonatal cpap

Abstract: The review mainly focuses on the goals to evaluate the clinical and cost effectiveness of neonatal CPAP in a decrease of Mortality, Length of Stay, Respiratory support, Extubation and Intubation. Introduction: Inclusion criteria: This review is conducted in neonates with respiratory failure, Pneumonia sepsis, necrotizing infections, Pneumothorax, Broncho pulmonary distress, respiratory distress syndrome (RDS), COVID-19, and other comorbidities also included. Methods: The databases like PubMed, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Mechanical ventilation can cause changes in lung air ow and blood gas levels, which can in turn affect blood ow in the brain, potentially leading to vessel rupture and bleeding [20,21]. Providing CPAP and PS assistance early during delivery has been proven to lessen the need for postnatal intubation [22][23][24]. Our research showed that infants who are unable to withdraw invasive ventilation within 1 week of birth are at a 3.668 times greater risk of developing PIVH than are those who on noninvasive ventilation.…”
Section: Risk Factors and Prediction For Pivh In The Elbwimentioning
confidence: 99%
“…Mechanical ventilation can cause changes in lung air ow and blood gas levels, which can in turn affect blood ow in the brain, potentially leading to vessel rupture and bleeding [20,21]. Providing CPAP and PS assistance early during delivery has been proven to lessen the need for postnatal intubation [22][23][24]. Our research showed that infants who are unable to withdraw invasive ventilation within 1 week of birth are at a 3.668 times greater risk of developing PIVH than are those who on noninvasive ventilation.…”
Section: Risk Factors and Prediction For Pivh In The Elbwimentioning
confidence: 99%